The evolution of endodontic files – literature review (Research, Society and Development, 2022)
Introduction: ProtaperUltimate File was an innovative advantage for the professional, because it allows to treat a wide variety of anatomical challenges in clinical practice, this system also allows the clinician to perform minimally invasive canal preparations, more as other files are not all 100% good, because there comes a time when the operator is using the file and it will fracture. Objective: To know the benefits of the evolution of endodontic files and their use in the treatment of root canals. Methodology: This is a literature review with a descriptive approach. Results: Stainless steel manual file features high resistance and hardness, allowing excellent control and precision on its cutting surfaces. File Nickel-Titanium (Ni-Ti) has greater elasticity, flexibility and resistance to fracture during torsional rotation. Between 2001 and 2006 the files Protaper, Protaper NEXT and Protaper Universal since both would improve resistance and flexibility throughout the work carried out with them. M-wire and R-phase files have higher fatigue strength and excellent flexibility. Results and Discussion: Reciproc files have greater resistance to flexural fatigue and WaveOne has greater torsional resistance. Lima WaveOne Gold is also the brand DentsplyMaillefer, it was introduced in the market as a new Reciprocating system that has greater resistance and flexibility. Conclusions: In this work, we searched the literature for an overview of the evolution of endodontic instruments over old to current files, elucidating the relevant points of the clinical practice of endodontics, facilitating the treatment of root canals by dentistry professionals.